Critical essays on Indian writing in English : presented to Armando Menezes - Menezes, Armando, 1902-; Naik, M. K.; Desai, S. K.; Amur, G. S. (Karnatak University ; distributors, Macmillan Co. of India, 1972)
Festschrift honoring Armando Menezes, b. 1902, Indian poet and educationist.